Incidencia de la Recaudación Tributaria en el PIB de Ecuador, período 2000 – 2014 - Ocampo Tirado, Luis Miguel (2016)
Taxes play an important role as permanent income generators that allow the economic and social development of the country. However, it considers that excessive tax system in their tariffs may end up affecting the development of the economic activities. Therefore, arises the question to know whether ¿Does it affect the collection of taxes in GDP? In order to respond to the raised problematic, it was proposed this research entitled: "The incidence of tax collection in GDP of Ecuador, 2000-2014 period". The general objective was to analyze the behavior of the Tax Collection and GDP of the Ecuadorian economy during 2000-2014 period, through the statistical process of time series in order to determine the incidence between both variables. To determine the incidence between both variables it was based on the theory of Laffer curve, which relates the level of taxes with tax collection, allowing study how taxes affect to the production. The research was developed under the scientific method with its different modalities, and the used techniques were: bibliographic and statistics. Consequently during the period of analysis it has been possible to demonstrate a significant increase in tax collection compared with permanent growth of the GDP that has only been affected by fluctuations in oil prices and the global crisis of 2008. The main extracted conclusion from the obtained results in the research process shows that tax collection from Ecuador has not affected the GDP, because the actual tax rate is not yet at its highest estimated point, that is, the tax pressure is lower than the potential, which allows increasing the level of taxes without affecting economic activity.